2009
DOI: 10.1074/jbc.m109.047449
|View full text |Cite
|
Sign up to set email alerts
|

N-terminal Domains Elicit Formation of Functional Pmel17 Amyloid Fibrils

Abstract: Pmel17 is a transmembrane protein that mediates the early steps in the formation of melanosomes, the subcellular organelles of melanocytes in which melanin pigments are synthesized and stored. In melanosome precursor organelles, proteolytic fragments of Pmel17 form insoluble, amyloid-like fibrils upon which melanins are deposited during melanosome maturation. The mechanism(s) by which Pmel17 becomes competent to form amyloid are not fully understood. To better understand how amyloid formation is regulated, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
156
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(165 citation statements)
references
References 57 publications
7
156
0
2
Order By: Relevance
“…S4B). When they have been released from the membrane in control cells, Mα fragments assemble into Triton X-100 (TX)-insoluble fibrils (12) and undergo further proteolytic processing to smaller fragments (detected by antibodies HMB45 and I51) (16,26,27) (Fig. S1A).…”
Section: Bace2 Releases Pmel Luminal Domain To Generate Amyloidogenicmentioning
confidence: 99%
See 1 more Smart Citation
“…S4B). When they have been released from the membrane in control cells, Mα fragments assemble into Triton X-100 (TX)-insoluble fibrils (12) and undergo further proteolytic processing to smaller fragments (detected by antibodies HMB45 and I51) (16,26,27) (Fig. S1A).…”
Section: Bace2 Releases Pmel Luminal Domain To Generate Amyloidogenicmentioning
confidence: 99%
“…S1A). They include (i) cleavage of the full-length transmembrane form of PMEL by a proprotein convertase (PC) into an amyloidogenic luminal Mα fragment and a disulfide-linked transmembrane domain-containing Mβ fragment (12), (ii) further cleavage of Mβ by an "endosomal" sheddase to release Mα linked to Mβ luminal domain (i.e., Mβ-N) from the transmembrane C-terminal fragment (CTF) and to allow Mα oligomerization to form amyloid fibrils (13,14), (iii) further processing of Mα by unknown proteases into smaller fragments found in mature fibrils and fibrillar sheets (15,16), and (iv) intramembrane proteolysis of the CTF by the γ-secretase complex (13,14). The analogy between the processing of PMEL and APP led us to investigate the role of BACE secretases in PMEL processing and functional amyloid formation.…”
mentioning
confidence: 99%
“…Though there is no current consensus as to which polypeptide domain solely or partly constitutes the Pmel17 amyloid core, recent results showed that both isolated luminal regions, RPT, residues 315-444 ( Fig. 1) (24) and the polycystic kidney disease-1 like domain, residues 201-314 (25) are sufficient for amyloid formation in vitro. While both domains are important for fibril formation in vivo (26), we choose RPTas a model system to study aggregation kinetics because prior observation revealed that RPT fibril stability is particularly pH sensitive (24).…”
mentioning
confidence: 99%
“…The conversion of full-length wild type and mutant Cdk5-phosphorylated PrPs occurs at physiological pH and temperature and in non-denaturant conditions, similar to that observed for the human Pmel17 Ma fragment, which readily converts into amyloid and forms the core of melanosomes (41). The IKTA reaction indicates first order kinetics for the Cdk5-mediated conversion of wild type and mutant full-length PrPs, similar to that obtained with other functional amyloid-forming proteins from fungi to mammals (41)(42)(43)(44)(45)(46)(47). Furthermore, the ThT-positive amyloid in PrP WT-V or Y145X M and the seeding properties of phosphorylated Q160X M were partially reversible upon dephosphorylation, similar to the reversibility of secretory granule peptide hormone amyloids as they convert to a monomeric ␣-helical form when released (45).…”
Section: Discussionmentioning
confidence: 71%